A Horizon Scan of Global Conservation Issues for 2016. (January 2016) - Sutherland, William J.; Broad, Steven; Caine, Jacqueline; Clout, Mick; Dicks, Lynn V.; Doran, Helen; Entwistle, Abigail C.; Fleishman, Erica; Gibbons, David W.; Keim, Brandon; LeAnstey, Becky; Lickorish, Fiona A.; et al.
Abstract : This paper presents the results of our seventh annual horizon scan, in which we aimed to identify issues that could have substantial effects on global biological diversity in the future, but are not currently widely well known or understood within the conservation community. Fifteen issues were identified by a team that included researchers, practitioners, professional horizon scanners, and journalists. The topics include use of managed bees as transporters of biological control agents, artificial superintelligence, electric pulse trawling, testosterone in the aquatic environment, building artificial oceanic islands, and the incorporation of ecological civilization principles into government policies in China. Trends: This is the seventh annual horizon scan. A team of 24 horizon scanners, researchers, practitioners, and journalists identified 15 issues following widespread consultation and a Delphi-like process to select the most suitable. The issues were wide ranging but included artificial superintelligence, changing costs of energy storage and consumptive models, and ecological civilization policies in China.